All-Atom and Coarse-Grained Molecular Dynamics Simulations of a Membrane Protein Stabilizing Polymer - Perlmutter, Jason D. (2011)
Amphipathic polymers called amphipols (APols) have been developed as an alternative to detergents for stabilizing membrane proteins (MPs) in aqueous solutions. APols provide MPs with a particularly mild environment and, as a rule, keep them in a native and functional state for longer periods than detergents do. Amphipol A8-35, a derivative of polyacrylate, is widely used and has been particularly well studied experimentally. In aqueous solutions, A8-35 molecules self-assemble into well-defined globular particles, with a mass of ~40 kDa and a R(g) of ~2.4 nm. As a first step towards describing MP/A8-35 complexes by molecular dynamics (MD), we present three sets of simulations of the pure APol particle. First, we performed a series of all-atom MD (AAMD) simulations of the particle in solution, starting from an arbitrary initial configuration. While AAMD simulations result in cohesive and stable particles over a 45-ns simulation, the equilibration of the particle organization is limited. This motivated the use of coarse-grained MD (CGMD), allowing us to investigate processes on the microsecond timescale, including de novo particle assembly. We present a detailed description of the parametrization of the CGMD model from the AAMD simulations, and a characterization of the resulting CGMD particles. Our third set of simulations utilizes reverse coarse-graining (rCG), through which we obtain all-atom coordinates from a CGMD simulation. This allows higher-resolution characterization of a configuration determined by a long-timescale simulation. An excellent agreement is observed between MD models and experimental, small angle neutron scattering data. The MD data provides new insights into the structure and dynamics of A8-35 particles, possibly relevant to the stabilizing effects of APols on MPs, as well as a starting point for modeling MP/A8-35 complexes.